REVIEWS (New blackfriars, 1971)
Review in this Article NEWMAN AND THE COMMON TRADITION. A Study in the Language of Church and Society, by John Coulson. THE VICTORIAN CHURCH IN DECLINE, by P. T. Marsh. EPHESIANS, BAPTISM AND PENTECOST, by J. C. Kirby. LET ME EXPLAIN, by Pierre Teilhard de Chardin. THE ONE AND THE MANY: TEILHARD DE CHARDIN'S VISION OF UNITY, by Donald Gray. MYTH: ITS MEANING AND FUNCTION IN ANCIENT AND OTHER CULTURES, by G. S. Kirk. BEHIND APPEARANCE: A study of the relations between painting and the natural sciences in this century, by C. H. Waddington. A VARIETY OF CATHOLIC MODERNISTS, by Alec Vidler.